Effects of Sugar Type and Concentration on Batu 55 Mandarin (Citrus reticulata Blanco.) Somatic Embryo Maturation - Wahyu Widoretno; Serafinah Indriyani; Chairani Martasari; Rikza Hakin (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
When obtaining plantlets, embryo maturation and simultaneous germination are important steps in plant micropropagation via somatic embryogenesis. Several studies have shown that the use of carbohydrates as a carbon source plays a significant role in inducing somatic embryo development in certain plant species. This study aimed to establish a somatic embryo maturation protocol for Batu 55 Mandarin (C. reticulata Blanco.) by examining the effect of various types of sugar and concentrations. The results showed that the type and concentration of sugar added to the medium affect the somatic embryo maturation of Batu 55 Mandarin. Galactose and maltose enhance somatic embryo maturation more effectively than does sorbitol. The combination of galactose or maltose with sorbitol was able to improve somatic embryo maturation more effectively than galactose or maltose alone. The combination of galactose and sorbitol enhanced the maturation of somatic embryos more effectively than did change the concentrations of maltose or sorbitol. It can be concluded that sugar type and concentration had effects on citrus somatic embryo development. The combination of sorbitol (36.5 mM) with galactose 73 mM was able to augment citrus somatic embryo maturation more effectively than the other concentrations applied.